PKM Pendampingan Penyusunan Laporan Keuangan Terintegrasi dan Perhitungan Perpajakan Pada Pelaku UMKM di Pasar Seni Sukawati Gianyar-Bali - Anak Agung Ayu Erna Trisnadewi; Anak Agung Sri Purnami; I Gusti Lanang Putra (Postgraduated Community Service Journal, 2024)
One of the MSMEs experiencing problems in financial management is MSME actors who are members of the Traders Association at the Sukawati Art Market, Gianyar-Bali. Sukawati Art Market is located in Sukawati Village, Sukawati District, Gianyar Regency, which is approximately 30 minutes from the east of Denpasar City. Sukawati Art Market provides clothes such as typical Balinese batik, apart from typical Balinese batik, there are also various kinds of shirts and shorts available. and long and also some t-shirts with Balinese patterns at low prices. All Sukawati Art Market items are negotiable and the price can be a third of the first day offered by the seller. So the Sukawati Art Market has become a favorite shopping place for tourists. Initial observations emphasize that MSME actors in the Sukawati art market have very low financial literacy and very minimal tax aspects. The solution provided is to provide counseling, training and assistance regarding the preparation of financial reports and tax calculations for MSMEs. The results of this community service activity include MSMEs starting to implement better financial practices, such as neater transaction recording and cash flow monitoring. Increased understanding of taxation, including tax obligations, types of applicable taxes, and the correct way to report taxes.